The translation of linguistic stereotypes in animated films: the case of DreamWorks films - Gonzalez Vera, Pilar (The Journal of Specialised Translation, 2012)
As a source for the socialisation of the child, animated films have attracted the attention of sociolinguistics which has traditionally been interested in the interaction between language and society. The role of language in the process of socialisation and in the creation and perpetuation of stereotypes is the focus of attention of this research. This study concentrates on the portrayal and translation of stereotypes on the basis of gender through the manipulation of the discourse in the DreamWorks' films Shrek and SharkTale. With this aim, the research is divided into three sections. The first one provides a brief introduction to the concept of stereotypes, the second is devotedto the study of the role of translation inthe representation of gender stereotypes in the cases of two female characters, Fiona and Lola, and two male characters, Donkey and Lenny; and the third one presents the conclusions drawn from the previous analysis.